The neuronal transcription factor Erect wing regulates specification and maintenance of Drosophila R8 photoreceptor subtypes - Hsiao, Hui-Yi (2013)
Signaling pathways are often re-used during development in surprisingly different ways. The Hippo tumor suppressor pathway is best understood for its role in the control of growth. The Hippo pathway is also used in a very different context, in the Drosophila eye for the robust specification of R8 photoreceptor neuron subtypes, which complete their terminal differentiation by expressing light-sensing Rhodopsin (Rh) proteins. A double negative feedback loop between the Warts kinase of the Hippo pathway and the PH-domain growth regulator Melted regulates the choice between `pale' R8 (pR8) fate defined by Rh5 expression and `yellow' R8 (yR8) fate characterized by Rh6 expression. Here, we show that the gene encoding the homologue of human Nuclear respiratory factor 1, erect wing (ewg), is autonomously required to repress warts and to promote melted expression to specify pR8 subtype fate and induce Rh5 expression. ewg mutants express Rh6 in most R8s due to ectopic warts expression. Further, ewg is continuously required to maintain repression of Rh6 in pR8s in aging flies. Our work shows that Ewg is a critical factor for the stable down-regulation of Hippo pathway activity to determine neuronal subtype fates. Neural-enriched factors, such as Ewg, may generally contribute to the contextual re-use of signaling pathways in post-mitotic neurons.